Juridical Analysis of Interlocking Directorate in the Perspective of Fiduciary Duty Theory - Selly Marlianti; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This article discusses the issue of concurrent positions of directors in a company has resurfaced in Indonesia, causing problems lately. The practice of holding multiple positions presents a potential avenue for individuals to exploit their authority for personal gain, as well as for the benefit of affiliated parties. The potential for conflicts of interest, including corruption, collusion, and nepotism, even exists in concurrent positions. The research method used is normative because what is studied is the legality of the interlocking directorate of directors and board of commissioners in the Company as seen from its regulations in the Law and other related regulations. This study focused on examining the legality of the interlocking directorate of directors and board of commissioners in PT. The result is that concurrent positions are not explicitly prohibited by the Limited Liability Company Law, but it is very important for the Board of Directors and the Board of Commissioners to have a ban on concurrent positions in the Company Regulations, Articles of Association, and Code of Ethics and Business Conduct. Code adherence ensures all stakeholders comply with company policies. Law Number 5 of 1999, especially Article 26, prohibits concurrent positions if the companies in which the directors serve are not in the same relevant market, have a close relationship, or jointly control the market share of certain goods and services, which has the potential to result in a monopoly. Unfair business practices and competition